Simultaneous Determination of Volatile Constituents from Acorus tatarinowii Schott in Rat Plasma by Gas Chromatography-Mass Spectrometry with Selective Ion Monitoring and Application in Pharmacokinetic Study - Xue Meng; Xinfeng Zhao; Shixiang Wang; Pu Jia; Yajun Bai; Sha Liao; Xiaohui Zheng (Journal of Analytical Methods in Chemistry)
A sensitive and specific gas chromatographic-mass spectrometry with selected ion monitoring (GC-MS/SIM) method has been developed for simultaneous identification and quantification of α-asarone, β-asarone, and methyl eugenol of Acorus tatarinowii Schott in rat plasma. Chromatographic separation was performed on a Restek Rxi-5MS capillary column (30 m × 0.32 mm × 0.25 μm), using 1-naphthol as internal standard (IS). MS detection of these compounds and IS was performed at m/z 178, 208, 208, and 144. Intra- and interday precisions of all compounds of interest were less than 10%. The recoveries are situated in the range of 92.4–105.2%. Pharmacokinetics of methyl eugenol confirmed to be one-compartment open model, α-asarone and β-asarone was two-compartment open model, respectively. The method will probably be an alternative to simultaneous determination and pharmacokinetic study of volatile ingredients in Acorus tatarinowii Schott.